2021
DOI: 10.1016/j.ajpath.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Calcium Homeostasis in Kidney Disease

Abstract: Calcium (Ca 2þ ) homeostasis is a crucial determinant of cellular function and survival. Endoplasmic reticulum (ER) acts as the largest intracellular Ca 2þ store that maintains Ca 2þ homeostasis through the ER Ca 2þ uptake pump, sarco/ER Ca 2þ ATPase, ER Ca 2þ release channels, inositol 1,4,5-trisphosphate receptor channel, ryanodine receptor, and Ca 2þ -binding proteins inside of the ER lumen. Alterations in ER homeostasis trigger ER Ca 2þ depletion and ER stress, which have been associated with the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 73 publications
(148 reference statements)
0
14
0
Order By: Relevance
“…The ER Ca 2+ homeostasis is mainly controlled by two Ca 2+ releasing channels, inositol 1,4,5-trisphosphate receptor (IP3R) and ryanodine receptor (RyR), and one Ca 2+ reuptake channel, sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA). Dysfunctions of these ER Ca 2+ channels cause a variety of kidney diseases, including ischemia/reperfusion (I/R)-induced tubular injury, autosomal dominant polycystic kidney disease (ADPKD), podocytopathy, and diabetic nephropathy [24]. It is reported that I/R induces renal tubule apoptosis when activation of IP3R starts a cascade of Ca 2+ release from the ER store [25].…”
Section: Endoplasmic Reticulum (Er) Ca 2+ Signaling Mediates Apoptosis In Kidney Diseasementioning
confidence: 99%
“…The ER Ca 2+ homeostasis is mainly controlled by two Ca 2+ releasing channels, inositol 1,4,5-trisphosphate receptor (IP3R) and ryanodine receptor (RyR), and one Ca 2+ reuptake channel, sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA). Dysfunctions of these ER Ca 2+ channels cause a variety of kidney diseases, including ischemia/reperfusion (I/R)-induced tubular injury, autosomal dominant polycystic kidney disease (ADPKD), podocytopathy, and diabetic nephropathy [24]. It is reported that I/R induces renal tubule apoptosis when activation of IP3R starts a cascade of Ca 2+ release from the ER store [25].…”
Section: Endoplasmic Reticulum (Er) Ca 2+ Signaling Mediates Apoptosis In Kidney Diseasementioning
confidence: 99%
“…Most secreted proteins, transmembrane proteins, and lipids are produced in the ER. In addition, the ER maintains cellular homeostasis by tightly regulating calcium dynamics, phospholipid biogenesis, and various intracellular signals by releasing Ca 2+ (Chevet et al 2001 ; Berridge 2002 ; Park et al 2021 ). Alterations in calcium levels and metabolism, redox imbalances, nutrient deprivation, and hypoxia can disrupt ER homeostasis (Schonthal 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…14 Sustained ER stress further induces large amounts of Ca 2+ to be rapidly released from calcium pools, disrupting the ER calcium balance and resulting in severe [Ca 2+ ] i dysregulation. 15 Reduced ER luminal Ca 2+ could exacerbate ER stress and apoptosis by disrupting calciumdependent chaperone functions and accumulating unfolded proteins, resulting in renal cell apoptosis, which exacerbates tissue injury. 16 (3) Dysfunction of cellular energy metabolism: The rapid degradation and massive consumption of ATP supply, loss of mitochondrial function caused by overproduction of ROS, and subsequent reduced ATP production all combine to overwhelm the cell's ability to maintain overall homeostasis and contribute to renal cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete mechanisms of kidney cell damage in the pathological process of AKI could include the following: (1) Intracellular Ca 2+ overload: During renal ischemia and hypoxia, the initial decrease in ATP causes depolarization of the cell membrane and activates the intracellular Na + –Ca 2+ exchange mechanism, which results in a massive extracellular Ca 2+ influx through the Ca 2+ channel. , (2) Oxidative stress injury: ATP is extensively degraded to hypoxanthine during renal ischemia and hypoxia, and hypoxanthine can further react with increased oxygen molecules during reperfusion, fueling the generation of massive amounts of reactive oxygen species (ROS). , Excessive ROS can not only damage organelle and plasma membranes, accelerating Ca 2+ influx via transmembrane ion transport perturbations, but also severely damage the structural functions of mitochondria and the endoplasmic reticulum (ER) . Sustained ER stress further induces large amounts of Ca 2+ to be rapidly released from calcium pools, disrupting the ER calcium balance and resulting in severe [Ca 2+ ] i dysregulation . Reduced ER luminal Ca 2+ could exacerbate ER stress and apoptosis by disrupting calcium-dependent chaperone functions and accumulating unfolded proteins, resulting in renal cell apoptosis, which exacerbates tissue injury .…”
Section: Introductionmentioning
confidence: 99%